Privacy Preserving Data Transmission in Malicious Vehicular Adhoc Networks - et. al., Mrs.R.M.Rajeshwari (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vehicle Adhoc Network is deployed on the road, where vehicles constitute mobile nodes in which active security and intelligent transportation are important applications of VANET. VANETs are a key part of the intelligent transportation systems (ITS) framework. Sometimes, VANETs are referred as Intelligent Transportation Networks. However, authentication and privacy of users are still two vital issues in VANETs. In the traditional mode, the transactional data storage provides no distributed and decentralized security, so that the third party initiates the dishonest behaviors possibly. VANET has temporary participants , communication between vehicles are short-lived messages. Possible situation might happens , adversary may play as an legitimate user and able to perform malicious activity .To address these challenges this paper proposes timestamp based message between users to perform secure data transmission and give the negligible probability of the attacker. With the help of Certificate Authority (CA) and the RoadSide Units (RSUs), our proposal attains the confidentiality and trace the identity of the unauthenticated vehicle in the anonymous announcements as well. Finally, through the theoretical analysis and simulations, our scheme is able to implement a secure VANET framework with accountability and privacy preservation